Fine-Tuning of the Actin Cytoskeleton and Cell Adhesion During Drosophila Development by the Unconventional Guanine Nucleotide Exchange Factors Myoblast City and Sponge. Issue 2 (23rd April 2015) - Biersmith, Bridget; Wang, Zong-Heng; Geisbrecht, Erika R
Abstract: The evolutionarily conserved Dock proteins function as unconventional guanine nucleotide exchange factors (GEFs). Upon binding to engulfment and cell motility (ELMO) proteins, Dock–ELMO complexes activate the Rho family of small GTPases to mediate a diverse array of biological processes, including cell motility, apoptotic cell clearance, and axon guidance. Overlapping expression patterns and functional redundancy among the 11 vertebrate Dock family members, which are subdivided into four families (Dock A, B, C, and D), complicate genetic analysis. In both vertebrate and invertebrate systems, the actin dynamics regulator, Rac, is the target GTPase of the Dock-A subfamily. However, it remains unclear whether Rac or Rap1 are the in vivo downstream GTPases of the Dock-B subfamily. Drosophila melanogaster is an excellent genetic model organism for understanding Dock protein function as its genome encodes one ortholog per subfamily: Myoblast city (Mbc; Dock A) and Sponge (Spg; Dock B). Here we show that the roles of Spg and Mbc are not redundant in the Drosophila somatic muscle or the dorsal vessel. Moreover, we confirm the in vivo role of Mbc upstream of Rac and provide evidence that Spg functions in concert with Rap1, possibly to regulate aspects of cell adhesion. Together these data show that Mbc and Spg can have different downstream GTPase targets. Our findings predict that the ability to regulate downstream GTPases is dependent on cellular context and allows for the fine-tuning of actin cytoskeletal or cell adhesion events in biological processes that undergo cell morphogenesis.